(untitled) (World Science, 2022)
Despite the development of innovative technologies, chorioamnionitis remains a pressing problem in modern obstetrics. The aim of our study was to determine the frequency of obstetric and perinatal complications in pregnant women with chorioamnionitis. The objective of our study was to determine the frequency of obstetrics and perinatal complications in pregnant women with chorioamnionitis. Study groups were formed: Group I (main) - 100 pregnant women with chorioamnionitis, Group II (control) - 100 women with physiological pregnancy. The condition of the mother-placenta-fetus system and the functional fetal condition were assessed by Doppler ultrasound and cardiotocography. The analysis of perinatal consequences in pregnant women with chorioamnionitis was performed, in particular, a retrospective study of perinatal mortality. In the main group of patients were observed the structural changes in placenta 3.9 times more than in group II, oligohydramnios and polyhydramnios 6.9 and 5.6 times more, respectively, intrauterine growth retardation stage I was observed in 11.0% of studied in the main group, intrauterine growth retardation stage II and III were found only in pregnant women of group I (54.0% and 6.0%), respectively. In the hemodynamic disorders structure is dominated by stage II, the degree of disorders is 62.0%, only in women with chorioamnionitis were observed disorders in the system "mother-placenta-fetus" stage III - 9.0%. Cardiotocography analysis defined signs of fetal cardiac reactivity in 85.0% of patients. The pathological course of childbirth significantly prevailed in the studied of the main group. Intrauterine infection was diagnosed in 21.0% of cases. Early neonatal sepsis was observed in 9 (42.9%) cases, necrotizing enterocolitis in 5 (23.8%) newborns, congenital pneumonia - 7 (33.3%) cases. In the structure of antenatal fetal death, chorioamnionitis in pregnant women was diagnosed in 63.6% of patients, in the structure of early neonatal mortality - 58.3% of cases. The results of the study indicate that intraamniotic infection is a risk factor for the development of pathological pregnancy and labor with relevant perinatal complications.